2005
DOI: 10.1007/s10464-005-8614-2
|View full text |Cite
|
Sign up to set email alerts
|

Family Protection and Prevention of Alcohol Use Among Hispanic Youth at High Risk

Abstract: Research regarding prevention strategies for Hispanic youth stress the importance of family interventions because of the particular importance of family as a protective factor within the Hispanic community. Starting in 1995, the Center for Substance Abuse Prevention conducted the National Cross-Site Evaluation of High Risk Youth Programs, a 5-year drug and alcohol prevention study with a sample of approximately 10,500 youth, including nearly 3,000 Hispanic youth. Youth were surveyed regarding their alcohol use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 13 publications
3
64
0
4
Order By: Relevance
“…These studies have been conducted frequently in other countries 8,11,12,15 . However, in Brazil, there are still few studies about this matter.…”
Section: Palavrasmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have been conducted frequently in other countries 8,11,12,15 . However, in Brazil, there are still few studies about this matter.…”
Section: Palavrasmentioning
confidence: 99%
“…A longitudinal study in the United States indicated several protective factors in families, including family connection and cohesion, as well as family supervision. These parental attitudes led to the reduced use of alcohol 15 . Another important factor is mental health.…”
Section: Introductionmentioning
confidence: 99%
“…In another study aimed to identify preventive family factors among Hispanic youth at risk of alcohol use, the results revealed that family factors (including family connectedness, family supervision, and parental attitudes towards their child's alcohol use) were highly linked to alcohol use especially among Hispanic females. Moreover, the results of this study indicated that improving the parent-youth connections can have positive long-term impacts on decreasing their alcohol use and promoting their resilience (12). Other studies showed that enhancing the level of perceived social support led to an increase in the level of resilience and aided people in coping with their problems and emotions (13,14).…”
Section: Introductionmentioning
confidence: 57%
“…The relationship of social support with resilience can be effective in decreasing emotional problems and psychological stress among young people (10)(11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…As pesquisas que investigam as práticas educativas parentais apontam que elas estão relacionadas a diversos comportamentos, tais como: comportamentos antissociais dos filhos (Salvador & Weber, 2005); habilidades sociais dos filhos (Löhr, 2003;Weber, Flor, Viezzer, & Gusso, 2004); com maior facilidade do filho em enfrentar situações estressoras (Clark, Novak, & Dupree, 2002;Meesters & Murris, 2004;Wolfradt, Hempel, & Miles, 2003); sintomas depressivos nos filhos (Darling, 1999;Menegatti, 2002;Sander & McCarty, 2005); sintomas ansiosos (Hudson & Rapee, 2001;Weber, Biscaia, Pavei, & Brandenburg, 2003;Wolfradt, Hempel & Miles, 2003); comportamento agressivo (Alvarenga & Piccini, 2001;Ferreira & Marturano, 2002;Oliveira, Marin, Pires, Frizzo, Ravanello, & Rossato, 2002;Salvo, Silvares, & Toni, 2005); e com o uso de drogas e substâncias ilícitas (Cottrell, LI, Harris, D'alessandri, Atkins, Richardson, & Stanton, 2003;Sale, Sambrano, Springer, Peña, Pan, & Kasim, 2005).…”
Section: Palabras Clave: Comportamiento Alimentar; Prácticas Educativunclassified